2018 IEEE 7th World Conference on Photovoltaic Energy Conversion (WCPEC) (A Joint Conference of 45th IEEE PVSC, 28th PVSEC &Amp 2018
DOI: 10.1109/pvsc.2018.8547804
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Optimal Ingot Resistivity for both the Cell Performances and the Temperature Coefficients for Different Cell Architectures

Abstract: Compensation engineering enables the achievement of lower ingot resistivities with relatively constant performances along the ingot height. In this paper the impact of the bulk resistivity on the cell performances and the temperature coefficients is investigated for compensated and non-compensated multicrystalline silicon. Based on experimental data we show that reducing the bulk resistivity below a certain value improves the temperature coefficients but deteriorates the cell performances for two distinct cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Ponce‐Alcántara et al 46 reported a wafer resistivity dependence of TC V oc of Si solar cells, which can be justified by the relative variation of the diode saturation current density with temperature (indicating γ variation). More directly, Berthod et al 47 attributed the wafer resistivity dependence of passivated emitter and rear (PERC) cells' TC V oc to a sensible difference in the value of γ . Note that the solar cells reported in the two studies have the same wafer thickness (180–200 μm) as our standard thickness cells.…”
Section: Resultsmentioning
confidence: 99%
“…Ponce‐Alcántara et al 46 reported a wafer resistivity dependence of TC V oc of Si solar cells, which can be justified by the relative variation of the diode saturation current density with temperature (indicating γ variation). More directly, Berthod et al 47 attributed the wafer resistivity dependence of passivated emitter and rear (PERC) cells' TC V oc to a sensible difference in the value of γ . Note that the solar cells reported in the two studies have the same wafer thickness (180–200 μm) as our standard thickness cells.…”
Section: Resultsmentioning
confidence: 99%
“…The different amounts of dopants may lead to band gap narrowing, affecting both and directly, as well as affecting the absorption of light in the material. Recent studies show, however, that the base resistivity is more important than the compensation for both the performance of the solar cell and its temperature coefficients [23], [24]. Quantum efficiencies (QE) measured at different temperatures show that the main difference is in the 800 to 1100 nm range indicating a bulk lifetime effect.…”
Section: Introductionmentioning
confidence: 99%